2023
DOI: 10.1021/acscentsci.3c00054
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Mpro Protease Variants of Concern Display Altered Viral Substrate and Cell Host Target Galectin-8 Processing but Retain Sensitivity toward Antivirals

Abstract: The main protease of SARS-CoV-2 (M pro ) is the most promising drug target against coronaviruses due to its essential role in virus replication. With newly emerging variants there is a concern that mutations in M pro may alter the structural and functional properties of protease and subsequently the potency of existing and potential antivirals. We explored the effect of 31 mutations belonging to 5 variants of concern (VOCs) on catalytic parameters and substrate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 66 publications
(143 reference statements)
6
15
0
Order By: Relevance
“…In purified form, T21I, L50F and L141R Mpro all showed elevated ac9vity (1.6, 1.7, and 1.9 fold increased enzyme proficiency compared to WT). The enzyme ac9vity of L50F and T21I have been reported by others, and also found to be increased by a small amount (1.6 fold and 1.3 fold respec9vely) compared to WT 14,15 . The ac9vity of L50F is somewhat controversial as two studies reported null ac9vity 11,12 and one report was unable to purify this variant 14 .…”
Section: Resultssupporting
confidence: 76%
“…In purified form, T21I, L50F and L141R Mpro all showed elevated ac9vity (1.6, 1.7, and 1.9 fold increased enzyme proficiency compared to WT). The enzyme ac9vity of L50F and T21I have been reported by others, and also found to be increased by a small amount (1.6 fold and 1.3 fold respec9vely) compared to WT 14,15 . The ac9vity of L50F is somewhat controversial as two studies reported null ac9vity 11,12 and one report was unable to purify this variant 14 .…”
Section: Resultssupporting
confidence: 76%
“…This enhancement in activity resulted from an increase in both binding affinity (K M ) and turnover rate (k cat ). In optimal buffer, there were no substantial changes in the kinetic constants of the protease variants toward the peptide substrate QS1, suggesting that the mutations did not change the active site space enough to affect the enzymes' function [7]. In contrast, the protease variants were noticeably different when analyzed using a protein substrate.…”
Section: Discussionmentioning
confidence: 95%
“…The HCoV genome encodes several nonstructural proteins that are synthesized as two large polyproteins pp1a and pp1ab, which are cleaved by the virus proteases named papain-like protease and the main protease (M pro ; EC3.4.22.69) [2]. The protease's primary role is to process the polyproteins pp1a and pp1ab, which mediate the functions required for viral replication and transcription [1,[3][4][5], and possibly also cleavage of host proteins [6,7]. The enzyme has a very stringent cleavage specificity, recognizing preferentially the sequence Leu-Gln↓ (Ser, Ala, Gly) [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous report demonstrated the effect of mutations in M pro from four VOCs on protease activity against viral and host substrates and furthermore showed no change in potency for nirmatrelvir. 49 To ensure that modifications in the chemical structure of 1 did not affect its ability to inhibit M pro from VOCs, we chose several variants with mutations close to the binding site of the drug.…”
Section: Effect Of Mutations In M Pro Of Vocs On the Potency Of Inhib...mentioning
confidence: 99%